Preparation method of positive electrode active material, positive electrode active material, battery and electric device

Through plasma-assisted ball milling treatment and sintering technology, a more complete and uniform carbon cladding layer is formed, solving the low conductivity problem of positive electrode materials such as lithium iron phosphate, and significantly improving the battery's magnification and low temperature performance.

CN119873779APending Publication Date: 2025-04-25GUANGZHOU AUTOMOBILE GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510012977.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The intrinsic electronic conductivity and ionic conductivity of positive electrode materials such as lithium iron phosphate are low, which affects their low temperature and rate performance. The existing carbon coating modification methods have problems such as poor dispersion, uneven coating and poor quality of carbon coating.

Method used

Through plasma-assisted ball milling treatment, the carbon source is initially coated with the original active material, and the carbon source is completely carbonized by sintering to form a more complete and uniform carbon coating layer.

Benefits of technology

The conductivity of the carbon cladding layer of the positive electrode active material and the diffusion rate of lithium ions are improved, and the rate performance and low-temperature performance of the battery are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873779A_ABST
    Figure CN119873779A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a positive electrode active material, the positive electrode active material, a battery and an electric device. The preparation method of the positive electrode active material comprises the following steps: adding a carbon source and an original active material into a ball milling tank of plasma-assisted ball milling equipment; the carbon source and the original active material are subjected to plasma-assisted ball milling treatment, so that the carbon source is preliminarily carbonized, a precursor is obtained, the precursor comprises precursor particles, the precursor particles comprise inner cores and precursor coating layers, the outer surfaces of the inner cores are covered with the precursor coating layers, the inner cores are original active material particles, and the precursor coating layers are formed by the carbon source; and sintering the precursor to completely carbonize the precursor coating layer and form a carbon coating layer, thereby obtaining the positive electrode active material. According to the preparation method of the positive electrode active material provided by the embodiment of the invention, the process is simple and controllable, the carbon coating layer in the prepared positive electrode active material is more complete and uniform, the carbonization is more sufficient, and the rate capability and low-temperature performance of the prepared battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a method for preparing a positive electrode active material, the positive electrode active material, a battery and an electrical device. Background Art

[0002] In the related technologies, positive electrode materials such as lithium iron phosphate are increasingly widely used in batteries due to their advantages of good safety, low cost and long cycle life. However, there are still some problems restricting the development of positive electrode materials such as lithium iron phosphate. For example, positive electrode materials such as lithium iron phosphate have the disadvantages of low intrinsic electronic conductivity and low intrinsic ionic conductivity.

[0003] The inherent low electronic conductivity and ionic conductivity of positive electrode materials such as lithium iron phosphate affect their low-temperature performance and rate performance. There are many modification schemes to address these problems, mainly including surface coating, nano-processing and element doping, among which surface carbon coating is the most common modification method.

[0004] However, the modification methods of positive electrode materials such as carbon-coated lithium iron phosphate in related technologies have problems such as poor dispersion, uneven and incomplete coating, and poor quality of the carbon coating layer, which makes the carbon coating layer not sufficiently improve the rate performance and low-temperature performance of the battery made of the positive electrode active material. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one purpose of the present invention is to propose a method for preparing a positive electrode active material, by subjecting a carbon source and an original active material to plasma-assisted ball milling, the carbon source initially coats the original active material, the plasma bombards the original active material and initially carbonizes the carbon source coated on the surface of the original active material, the energy generated during the plasma-assisted ball milling is high, the local temperature can be high, and the material is easier to melt, which enables the carbon source to better adhere to the surface of the original active material, thereby facilitating the formation of a more complete and uniform carbon coating layer; and, by sintering the precursor, the carbon source coated on the surface of the original active material can be more fully carbonized, the process of the method is simple and controllable, and the carbon coating layer in the prepared positive electrode active material is more complete and uniform, which can improve the rate performance and low temperature performance of the prepared battery.

[0006] The present invention also provides a positive electrode active material prepared by the positive electrode active material preparation method.

[0007] The present invention also provides a battery comprising the positive electrode active material.

[0008] The present invention also provides an electrical device comprising the battery.

[0009] According to the first aspect of the present invention, the method for preparing positive electrode active materials includes: adding a carbon source and an original active material into a ball milling jar of a plasma-assisted ball milling device; performing plasma-assisted ball milling on the carbon source and the original active material to preliminarily carbonize the carbon source, thereby obtaining a precursor, wherein the precursor includes precursor particles, and the precursor particles include an inner core and a precursor coating layer, wherein the precursor coating layer covers the outer surface of the inner core, the inner core is an original active material particle, and the precursor coating layer is formed by the carbon source; and sintering the precursor to completely carbonize the precursor coating layer and form a carbon coating layer, thereby obtaining the positive electrode active material.

[0010] According to the preparation method of the positive electrode active material of the embodiment of the present invention, the carbon source and the original active material are subjected to plasma-assisted ball milling treatment, the carbon source initially coats the original active material, the plasma bombards the original active material and initially carbonizes the carbon source coated on the surface of the original active material. The energy generated during the plasma-assisted ball milling treatment is high, which can make the local temperature higher and make the material easier to melt, so that the carbon source can better adhere to the surface of the original active material, thereby facilitating the formation of a more complete and uniform carbon coating layer; and, by sintering the precursor, the carbon source coated on the surface of the original active material can be more fully carbonized. The process of this method is simple and controllable, and the carbon coating layer in the prepared positive electrode active material is more complete and uniform, which can improve the rate performance and low temperature performance of the prepared battery.

[0011] According to some embodiments of the present invention, the mass ratio of the carbon source to the original active material is 5% to 25%.

[0012] According to some embodiments of the present invention, the process parameters for plasma-assisted ball milling of the carbon source and the original active material include: the rotation speed of the ball mill is 900 rpm to 1000 rpm, the ball milling time is 30 min to 60 min, and the discharge current is 2 A to 2.5 A.

[0013] According to some embodiments of the present invention, the process parameters for plasma-assisted ball milling of the carbon source and the original active material include: a ball milling system, wherein the ball milling system includes:

[0014] The plasma-assisted ball milling device works and stops alternately, a single working cycle duration of the plasma-assisted ball milling device is a working cycle duration, and a single stopping cycle duration of the plasma-assisted ball milling device is a stopping cycle duration.

[0015] According to some embodiments of the present invention, the working cycle duration ranges from 3 minutes to 8 minutes, and the stop cycle duration ranges from 3 minutes to 8 minutes.

[0016] According to some embodiments of the present invention, the ball milling medium in the ball milling jar is a grinding ball, and the diameter of the grinding ball is 2 mm to 5 mm; and / or the ball-to-material ratio of the ball milling is 5:1 to 10:1.

[0017] According to some embodiments of the present invention, the process of sintering the precursor includes:

[0018] Raising the temperature to a first calcination temperature at a first heating rate, and calcining at the first calcination temperature for a first preset time;

[0019] The temperature is raised to a second calcination temperature at a second heating rate, and calcined at the second calcination temperature for a second preset time, and then annealed as the furnace is cooled, wherein the second calcination temperature is greater than the first calcination temperature.

[0020] According to some embodiments of the present invention, the first heating rate is 4°C / min to 6°C / min, the first calcination temperature is 280°C to 350°C, and the first calcination time is 2h to 3h; the second heating rate is 4°C / min to 6°C / min, the second calcination temperature is 560°C to 650°C, and the second calcination time is 3h to 5h.

[0021] According to some embodiments of the present invention, after adding the carbon source and the original active material into the ball milling tank of the plasma-assisted ball milling device and before subjecting the carbon source and the original active material to plasma-assisted ball milling, the method further comprises:

[0022] The ball mill jar is subjected to a gas washing operation, which includes: evacuating the ball mill jar, and introducing argon gas after the evacuation, so that the gas pressure in the ball mill jar reaches a preset pressure.

[0023] According to some embodiments of the present invention, the scrubbing operation is repeated 2-3 times.

[0024] According to some embodiments of the present invention, the preset air pressure is 0.9-1.1 standard atmospheric pressure.

[0025] According to some embodiments of the present invention, the carbon source includes DL-malic acid; and / or the original active material includes at least one of lithium iron phosphate, lithium manganese phosphate and lithium manganese iron phosphate.

[0026] According to the positive electrode active material of the second embodiment of the present invention, the positive electrode active material is prepared by the preparation method of the positive electrode active material of the first embodiment of the present invention, the positive electrode active material includes positive electrode active material particles, the positive electrode active material particles include an inner core and a carbon coating layer, and the carbon coating layer is coated on the outer surface of the inner core.

[0027] According to the positive electrode active material of the embodiment of the present invention, which is prepared by the method for preparing the positive electrode active material according to the embodiment of the first aspect of the present invention, the carbon coating layer covers the inner core more evenly and fully, the conductivity of the carbon coating layer is stronger, and the diffusion rate of lithium ions is greater, which can improve the rate performance and low temperature performance of the prepared battery.

[0028] A battery according to an embodiment of the third aspect of the present invention comprises: a positive electrode plate and a negative electrode plate, wherein the positive electrode plate comprises a positive electrode collector and a positive electrode active material covering the positive electrode collector, and the positive electrode active material is the positive electrode active material according to an embodiment of the second aspect of the present invention.

[0029] According to the battery of the embodiment of the present invention, by including the positive electrode active material according to the embodiment of the second aspect of the present invention, the carbon coating layer of the positive electrode active material covers the inner core more evenly and fully, the conductivity of the carbon coating layer is stronger, and the diffusion rate of lithium ions is greater, which can improve the rate performance and low temperature performance of the manufactured battery.

[0030] The electrical device according to the fourth embodiment of the present invention is characterized by comprising: a battery according to the third embodiment of the present invention.

[0031] According to the electrical device of the embodiment of the present invention, by including the battery according to the embodiment of the third aspect of the present invention, the carbon coating layer of the positive electrode active material in the battery more evenly and fully coats the inner core, the carbon coating layer has stronger conductivity and a greater diffusion rate of lithium ions, which can improve the rate performance and low temperature performance of the manufactured battery.

[0032] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0034] Figure 1 is an XRD diagram of a positive electrode active material according to some embodiments of the present invention and a positive electrode active material in a related art;

[0035] Figure 2 are SEM images of positive electrode active materials according to some embodiments of the present invention and positive electrode active materials in related arts, wherein (a) is the SEM image of Embodiment 1, (b) is the SEM image of Embodiment 2, and (c) is the SEM image of Comparative Example 1;

[0036] Figure 3TEM images of positive electrode active materials according to some embodiments of the present invention and positive electrode active materials in related arts, wherein (a) is a TEM image of Embodiment 1, (b) is an enlarged image of the TEM of Embodiment 1, (c) is a TEM image of Embodiment 2, (d) is an enlarged image of the TEM of Embodiment 2, (e) is a TEM image of Comparative Example 1, and (f) is an enlarged image of the TEM of Comparative Example 1;

[0037] Figure 4 is the cycle performance of the positive electrode active material according to some embodiments of the present invention and the positive electrode active material in the related art at 10C at 30°C;

[0038] Figure 5 is the rate performance of the positive electrode active material according to some embodiments of the present invention and the positive electrode active material in the related art at 30° C.;

[0039] Figure 6 It is the cycle performance of the positive electrode active materials according to some embodiments of the present invention and the positive electrode active materials in the related art at 0.5C at -10°C. DETAILED DESCRIPTION

[0040] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0041] Reference below Figure 1-Figure 6 A method for preparing a positive electrode active material according to an embodiment of the present invention is described.

[0042] A method for preparing a positive electrode active material according to a first embodiment of the present invention comprises:

[0043] Adding the carbon source and the raw active material into the ball milling tank of the plasma-assisted ball milling device;

[0044] The carbon source and the original active material are subjected to plasma-assisted ball milling treatment to initially carbonize the carbon source, thereby obtaining a precursor. The ball milling treatment can make the carbon source more fully cover the original active material in the process. By adding plasma-assisted treatment, the plasma can bombard the original active material and initially carbonize the carbon source coated on the surface of the original active material, which can make the carbonization of the carbon source more complete. In addition, the high energy generated during the plasma-assisted ball milling treatment can make the local temperature higher, making the material easier to melt, which allows the carbon source to better adhere to the surface of the original active material, thereby facilitating the formation of a more complete and uniform carbon coating layer.

[0045] The precursor includes precursor particles, the precursor particles include a core and a precursor coating layer, the precursor coating layer covers the outer surface of the core, the core is an original active material particle, the precursor coating layer is formed by a carbon source, and the precursor particles obtained by plasma-assisted ball milling have a precursor coating layer on the surface that more fully coats the core, and the surface precursor coating layer is more fully carbonized, and has better conductivity;

[0046] The precursor is sintered to completely carbonize the precursor coating and form a carbon coating, thereby obtaining a positive electrode active material. By sintering the precursor, the carbon coating of the positive electrode active material can be more fully carbonized, making the conductivity of the carbon coating stronger and improving the rate performance of the battery; and the positive electrode active material obtained by this method can include a layer of carbon coating uniformly coated on the surface, and the transport rate of lithium ions in the carbon coating is greater, which can improve the low temperature performance of the battery.

[0047] According to the preparation method of the positive electrode active material of the embodiment of the present invention, the carbon source and the original active material are subjected to plasma-assisted ball milling treatment, the carbon source initially coats the original active material, the plasma bombards the original active material and initially carbonizes the carbon source coated on the surface of the original active material. The energy generated during the plasma-assisted ball milling treatment is high, which can make the local temperature higher and make the material easier to melt, so that the carbon source can better adhere to the surface of the original active material, thereby facilitating the formation of a more complete and uniform carbon coating layer; and, by sintering the precursor, the carbon source coated on the surface of the original active material can be more fully carbonized. The process of this method is simple and controllable, and the carbon coating layer in the prepared positive electrode active material is more complete and uniform, which can improve the rate performance and low temperature performance of the prepared battery.

[0048] According to some embodiments of the present invention, the mass ratio of the carbon source to the original active material is 5% to 25%. For example, the mass ratio of the carbon source to the original active material can be 5%, 10%, 15%, 20%, 25%, etc. By making the mass ratio of the carbon source to the original active material not less than 5%, the content of the carbon source can be more sufficient, so that the carbon source can be more fully coated on the surface of the original active material; by making the mass ratio of the carbon source to the original active material not more than 25%, it is possible to avoid waste of raw materials while ensuring that the carbon source can fully coat the original active material.

[0049] According to some embodiments of the present invention, the process parameters for plasma-assisted ball milling of the carbon source and the original active material include: the rotation speed of the ball mill is 900rpm to 1000rpm, the ball milling time is 30min to 60min, and the discharge current is 2A to 2.5A. For example, the rotation speed of the ball mill can be 900rpm, 920rpm, 940rpm, 960rpm, 980rpm, 1000rpm, etc.; the ball milling time can be 30min, 40min, 50min, 60min, etc.; the discharge current can be 2A, 2.1A, 2.2A, 2.3A, 2.4A, 2.5A, etc. By setting the rotation speed of the ball mill to 900rpm to 1000rpm and the ball milling time to 30min to 60min, the carbon source can be more fully coated on the original active material; by setting the discharge current to 2A to 2.5A, the current can ensure that the carbon source can be more fully carbonized while avoiding wasting energy.

[0050] According to some embodiments of the present invention, the process parameters for plasma-assisted ball milling of the carbon source and the original active material include: a ball milling system, wherein the ball milling system includes:

[0051] The plasma-assisted ball milling equipment works and stops alternately, and the duration of a single working cycle of the plasma-assisted ball milling equipment is the working cycle duration, and the duration of a single stopping cycle of the plasma-assisted ball milling equipment is the stopping cycle duration. Since the plasma-assisted ball milling equipment needs to be powered on to make the gas in the equipment glow, if the power-on time is too long, it is easy to cause local high temperature in the equipment, which may cause equipment damage such as damage to the electrode rod. By making the ball milling system include the plasma-assisted ball milling equipment working and stopping alternately, the plasma-assisted ball milling equipment can be properly cooled during the stop cycle, so that the carbon source can be initially carbonized while protecting the plasma-assisted ball milling equipment to avoid local high temperature in the equipment and causing equipment damage.

[0052] According to some embodiments of the present invention, the working cycle duration ranges from 3min to 8min, and the stop cycle duration ranges from 3min to 8min. For example, the working cycle duration can be 3min, 4min, 5min, 6min, 7min, 8min, etc.; the stop cycle duration can be 3min, 4min, 5min, 6min, 7min, 8min, etc. By making the working cycle duration range from 3min to 8min and the stop cycle duration range from 3min to 8min, the carbon source can be initially carbonized while protecting the plasma-assisted ball milling equipment to avoid local high temperature of the equipment and causing equipment damage; and the process time can be shortened to improve production efficiency.

[0053] According to some embodiments of the present invention, the ball milling medium in the ball milling jar is a grinding ball, and the diameter of the grinding ball is 2 mm to 5 mm. For example, the diameter of the grinding ball can be 2 mm, 3 mm, 4 mm, 5 mm, etc. By making the diameter of the grinding ball 2 mm to 5 mm, the carbon source and the original active material can be fully mixed, so that the carbon source can cover the original active material more fully.

[0054] For example, the grinding balls may be stainless steel balls.

[0055] According to some embodiments of the present invention, the ball-to-material ratio of ball milling is 5:1 to 10:1. The ball-to-material ratio of ball milling refers to the mass ratio between the ball milling medium and the material. For example, the ball-to-material ratio of ball milling can be 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc. By making the ball-to-material ratio of ball milling 5:1 to 10:1, the carbon source and the original active material can be fully mixed, so that the carbon source can more fully coat the original active material; and the particle breakage of the prepared positive electrode active material can be avoided.

[0056] According to some embodiments of the present invention, the process of sintering the precursor includes:

[0057] Raising the temperature to a first calcination temperature at a first heating rate, and calcining at the first calcination temperature for a first preset time;

[0058] The temperature is raised to a second calcination temperature at a second heating rate, and calcined at the second calcination temperature for a second preset time, and then annealed as the furnace is cooled, and the second calcination temperature is greater than the first calcination temperature.

[0059] For example, the second calcination temperature is higher than the first calcination temperature.

[0060] For example, the process of sintering the precursor also includes:

[0061] After calcining at a second calcining temperature for a second preset time, annealing is performed as the furnace cools. By including an annealing process in the process of sintering the precursor, the defects of the carbon coating layer can be reduced, the structural strength of the carbon coating layer of the prepared positive electrode active material can be improved, and the integrity of the particles in the positive electrode active material can be more fully guaranteed; and the particle size of the particles in the positive electrode active material can be prevented from increasing, making it easier to control the particle size of the particles in the positive electrode active material.

[0062] According to some embodiments of the present invention, the first heating rate is 4°C / min to 6°C / min, the first calcination temperature is 280°C to 350°C, and the first calcination time is 2h to 3h; the second heating rate is 4°C / min to 6°C / min, the second calcination temperature is 560°C to 650°C, and the second calcination time is 3h to 5h. In the process of heating to the first calcination temperature at the first heating rate and calcining at the first calcination temperature for the first preset time, the precursor can be preheated to prevent the calcination temperature from being too high and causing damage to the particles in the precursor. By making the first heating rate 4°C / min to 6°C / min, the first calcination temperature 280°C to 350°C, and the first calcination time 2h to 3h, the preheating process of the precursor is more sufficient, and the integrity of the particles in the prepared positive electrode active material is more fully guaranteed; in the process of heating to the first calcination temperature at the second heating rate In the process of heating the battery to a second calcination temperature and calcining at the second calcination temperature for a second preset time, the carbon source can be fully carbonized, so that the conductivity of the carbon coating layer in the prepared positive electrode active material is stronger, and the rate performance of the battery is improved. By making the second heating rate 4°C / min to 6°C / min, the second calcination temperature 560°C to 650°C, and the second calcination time 3h to 5h, the carbon source in the carbon coating layer can be more fully carbonized, and the conductivity of the carbon coating layer in the prepared positive electrode active material can be more fully improved.

[0063] According to some embodiments of the present invention, after adding the carbon source and the original active material into the ball milling tank of the plasma-assisted ball milling device and before subjecting the carbon source and the original active material to the plasma-assisted ball milling treatment, the method further includes:

[0064] For the ball mill tank gas washing operation, the gas washing operation includes:

[0065] The ball mill is evacuated and then argon gas is introduced to make the air pressure in the ball mill reach the preset pressure.

[0066] By evacuating the ball mill, the original air in the ball mill can be removed to prevent the oxygen in the air from oxidizing the ions in the original active material, such as oxidizing the ferrous ions, and protecting the original active material. By introducing argon after evacuating the vacuum, the air pressure in the ball mill can be raised to the preset pressure, and the original active material can be protected from oxidation; and, since the ignition voltage for argon is low, it is easier to generate plasma in the ball mill during the process.

[0067] According to some embodiments of the present invention, the scrubbing operation is repeated 2-3 times. By repeating the scrubbing operation 2-3 times, residual air in the ball mill can be more fully avoided, and oxygen in the air can be prevented from oxidizing ions in the original active material, such as ferrous ions, so that the original active material is more fully protected.

[0068] According to some embodiments of the present invention, the preset air pressure is 0.9-1.1 standard atmospheric pressure. For example, the preset air pressure can be 0.9 standard atmospheric pressure, 0.95 standard atmospheric pressure, 1.0 standard atmospheric pressure, 1.05 standard atmospheric pressure, 1.1 standard atmospheric pressure, etc. By setting the preset air pressure to not less than 0.9 standard atmospheric pressure, the ball mill can work more stably and safely, and the electrode rod can be prevented from being punctured and burned; by setting the preset air pressure to not more than 1.1 standard atmospheric pressure, the danger caused by excessive air pressure can be avoided.

[0069] According to some embodiments of the present invention, the carbon source includes DL-malic acid. Since the temperature required for the decomposition of DL-malic acid is relatively low, by making the carbon source include DL-malic acid, the carbon coating layer of the prepared positive electrode active material can have a higher degree of graphitization, and the conductivity of the carbon coating layer is better, which can improve the rate performance of the battery.

[0070] According to some embodiments of the present invention, the original active material includes at least one of lithium iron phosphate, lithium manganese phosphate and lithium iron manganese phosphate. Among them, lithium iron phosphate can provide ferrous ions and lithium ions, lithium manganese phosphate can provide manganese ions, and lithium iron manganese phosphate can provide manganese ions, ferrous ions and lithium ions.

[0071] For example, the original active material may include lithium iron phosphate.

[0072] For example, the original active material may include lithium manganese phosphate.

[0073] For example, the original active material may include lithium iron manganese phosphate.

[0074] As another example, the original active material may include lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate.

[0075] According to the positive electrode active material of the second embodiment of the present invention, the positive electrode active material is prepared by the preparation method of the positive electrode active material of the first embodiment of the present invention, and the positive electrode active material includes positive electrode active material particles, and the positive electrode active material particles include an inner core and a carbon coating layer, and the carbon coating layer is coated on the outer surface of the inner core.

[0076] According to the positive electrode active material of the embodiment of the present invention, which is prepared by the method for preparing the positive electrode active material according to the embodiment of the first aspect of the present invention, the carbon coating layer covers the inner core more evenly and fully, the conductivity of the carbon coating layer is stronger, and the diffusion rate of lithium ions is greater, which can improve the rate performance and low temperature performance of the prepared battery.

[0077] A battery according to an embodiment of the third aspect of the present invention comprises: a positive electrode plate and a negative electrode plate, the positive electrode plate comprises a positive electrode collector and a positive electrode active material covering the positive electrode collector, and the positive electrode active material is the positive electrode active material according to an embodiment of the second aspect of the present invention.

[0078] According to the battery of the embodiment of the present invention, by including the positive electrode active material according to the embodiment of the second aspect of the present invention, the carbon coating layer of the positive electrode active material covers the inner core more evenly and fully, the conductivity of the carbon coating layer is stronger, and the diffusion rate of lithium ions is greater, which can improve the rate performance and low temperature performance of the manufactured battery.

[0079] The electrical device according to the fourth embodiment of the present invention is characterized by comprising: a battery according to the third embodiment of the present invention.

[0080] According to the electrical device of the embodiment of the present invention, by including the battery according to the embodiment of the third aspect of the present invention, the carbon coating layer of the positive electrode active material in the battery more evenly and fully coats the inner core, the carbon coating layer has stronger conductivity and a greater diffusion rate of lithium ions, which can improve the rate performance and low temperature performance of the manufactured battery.

[0081] The positive electrode active material and the preparation method thereof according to the embodiments of the present invention are further described below in combination with some embodiments of the present invention and comparative examples.

[0082] Example 1

[0083] (1) Preparation of precursor

[0084] Weigh 0.3g DL-malic acid and 2g LFP, mix and add into 0.2L stainless steel lined plasma ball mill, add 2mm stainless steel balls, the ball to material ratio is 10:1, seal the ball mill, evacuate and fill with 1 standard atmospheric pressure high-purity argon, repeat the above process 3 times for gas washing. Then, the ball mill with 1 standard atmospheric pressure argon atmosphere inside is milled on a plasma ball mill, the ball milling speed is 960rpm, the ball milling time is 60min, the discharge current is 2A, and the ball milling system is a cycle of working for 5min and stopping for 5min until the ball milling time is reached, and the powder is taken to obtain the precursor.

[0085] (2) Preparation of positive electrode active materials

[0086] The precursor in (1) was sintered at 300° C. for 2 h in a tube furnace under a 5% hydrogen-argon mixed atmosphere, and then heated to 600° C. for 3 h to obtain a carbon-coated secondary modified positive electrode active material.

[0087] (3) Preparation of positive electrode sheet

[0088] The positive electrode active material, conductive carbon (C45) and binder polyvinylidene fluoride (PVDF) containing N-methyl-2-pyrrolidone (NMP) in (2) are mixed in a mass ratio of 8:1:1, and stirred for 40 minutes using a degassing machine to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on one side of a clean aluminum foil surface, and after drying and cutting, a positive electrode sheet for testing is obtained.

[0089] (4) Preparation of button half-cell

[0090] In a glove box with a moisture and oxygen content of less than 10 ppm and filled with argon, the positive electrode sheet in (2) was used, a lithium sheet was used as the negative electrode, an electrolyte of 1 mol / L LiPF6 (the solvent was EC:DEC=1:2 Vol%, and 10% FEC was added), and a PP / PE / PP composite separator with a thickness of 25 μm was used to assemble a CR2025 button cell.

[0091] (5) Button cell electrochemical performance test

[0092] The battery was activated at 30°C for 3 cycles by charging to 4.0V at a constant current of 0.1C and then discharging to 2.5V at a constant current. The battery was then tested for 500 cycles at 30°C by charging to 4.0V at a constant current of 10C and then discharging to 2.5V at a constant current. The 30°C cycle performance data is shown in Figure 4 .

[0093] The 30℃ rate performance test was performed for 5 cycles at a constant current of 0.1C, 0.5C, 1C, 2C, 5C, 10C, and 0.1C respectively, charging to 4.0V and then discharging to 2.5V at a constant current. The 30℃ rate performance data is shown in Figure 5 .

[0094] The battery was activated at -10℃ for 3 cycles by charging to 4.0V at a constant current of 0.1C and then discharging to 2.5V at a constant current. The battery was then tested for 200 cycles at -10℃ by charging to 4.0V at a constant current of 0.5C and then discharging to 2.5V at a constant current. The low temperature cycle performance data at -10℃ is shown in the table. Figure 6 .

[0095] Example 2

[0096] The difference between this embodiment and embodiment 1 is that in the preparation of the precursor, the current of the plasma-assisted ball milling is 2.5 A and the ball milling time is 30 min. The remaining operations are carried out according to the same steps as in embodiment 1 to prepare the positive electrode active material, prepare the positive electrode sheet and conduct electrochemical performance test.

[0097] Comparative Example 1

[0098] The difference between this comparative example and Example 1 is that a positive electrode active material in the related art is selected as the comparative example, and the remaining operations are carried out according to the same steps as Example 1 to prepare the positive electrode sheet and perform electrochemical performance tests.

[0099] Figure 1 The XRD diagrams of positive electrode active material Example 1, Example 2 and Comparative Example 1 are shown in FIG. Figure 1 It can be seen that the characteristic peaks of the materials are all Pnma space group structures, which can correspond to the characteristic peaks of the standard card PDF#96-400-1848. Compared with the comparative example 1, the characteristic peaks of XRD in Example 1 and Example 2 are well matched, and it can be seen that the material after carbon coating still maintains the original crystal structure without being destroyed.

[0100] Figure 2 The SEM images of positive electrode active materials of Example 1, Example 2 and Comparative Example 1 show that the particle morphology and particle size of Example 1 and Example 2 are similar to those of Comparative Example 1, the particles themselves are not destroyed, and the carbon between the particles is more obvious.

[0101] Figure 3 The TEM images of positive electrode active material Example 1, Example 2 and Comparative Example 1 show that the positive electrode active material of Comparative Example 1, which is not modified by carbon coating, has sporadic flocculent carbon on the particle surface, and there are a large number of areas without carbon coating, making it difficult to form a uniform and complete carbon coating layer. Compared with Comparative Example 1, the state of the carbon coating layer on the particle surface of Example 1 and Example 2 is significantly improved, and the carbon coating layer on the surface is more complete, forming a complete carbon coating layer with a thickness of about 5-10 nm, which is conducive to further improving the performance of the positive electrode active material.

[0102] Figure 4 The positive electrode active material Example 1, Example 2 and Comparative Example 1 were installed into button-type batteries, and the 10C cycle test results were performed at 30°C. Figure 4It can be seen that after three cycles of 0.1C activation process, the initial specific capacities of the three materials at 30°C and 10C rate are 101.2 mAh / g, 103.2 mAh / g and 99.2 mAh / g, respectively. The discharge specific capacities of Example 1 and Example 2 are slightly higher than that of Comparative Example 1, and after a certain number of cycles, the capacity difference between Example 1, Example 2 and Comparative Example 1 is further increased. After 100 cycles, the discharge specific capacities of the three materials are 102.5 mAh / g, 103.5 mAh / g and 88.8 mAh / g, respectively. After 500 cycles, the discharge specific capacities of the three materials are 100.7 mAh / g, 101.8 mAh / g and 83.6 mAh / g, respectively, and the capacity retention rates are 99.51%, 98.64% and 84.27%, respectively. The cycle retention rates of the two carbon-coated positive electrode active materials are much higher than those of the positive electrode active materials in the related art that have not been coated, and have better high-rate cycle performance.

[0103] Figure 5 The results of the rate performance tests of positive electrode active materials of Example 1, Example 2 and Comparative Example 1 at 30°C and 0.1 / 0.5 / 1 / 2 / 5 / 10C. Figure 5 It can be seen that the specific capacities of the three materials are similar at low rates. As the current density increases, the specific capacity gap between Example 1, Example 2 and Comparative Example 1 gradually increases. The average discharge specific capacities of the three materials at a rate of 10C are 112.6 mAh / g, 109.22 mAh / g and 92.72 mAh / g, respectively, and the average discharge specific capacities at a rate of 5C are 127.82 mAh / g, 129 mAh / g and 111.4 mAh / g, respectively. The high rate performance of the two carbon-coated positive electrode active materials is much higher than that of the positive electrode active materials in the related art that are not coated.

[0104] Figure 6 The 0.5C cycle test results of positive electrode active materials Example 1, Example 2, and Comparative Example 1 were performed at -10°C. Figure 6 It can be seen that after three cycles of 0.1C activation process, the initial specific capacities of the three materials at -10°C and 0.5C rate were 80.7mAh / g, 80.9mAh / g and 65.7mAh / g, respectively. After 200 cycles, the discharge specific capacities of the three materials were 81.9mAh / g, 83.3mAh / g and 73mAh / g, respectively. The capacity retention rates of the three positive active materials at -10°C compared to 30°C were 50.72%, 50.81% and 42.77%, respectively. The specific capacities of the two carbon-coated positive active materials at low temperatures are significantly higher than those of the positive active materials in the related art that have not been coated, and have better low-temperature performance.

[0105] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0106] In the description of the present invention, "first feature" or "second feature" may include one or more of the features.

[0107] In the description of the present invention, "plurality" means two or more.

[0108] In the description of the present invention, a first feature being “on” or “under” a second feature may include that the first and second features are directly in contact with each other, or may include that the first and second features are not in direct contact with each other but are in contact with each other via another feature therebetween.

[0109] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0110] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for preparing a positive electrode active material, characterized in that: include: Adding the carbon source and the raw active material into the ball milling tank of the plasma-assisted ball milling device; The carbon source and the original active material are subjected to plasma-assisted ball milling treatment to preliminarily carbonize the carbon source, thereby obtaining a precursor, wherein the precursor comprises precursor particles, the precursor particles comprise a core and a precursor coating layer, the precursor coating layer covers the outer surface of the core, the core is the original active material particle, and the precursor coating layer is formed by the carbon source; The precursor is sintered to completely carbonize the precursor coating layer and form a carbon coating layer, thereby obtaining the positive electrode active material.

2. The method for preparing a positive electrode active material according to claim 1, characterized in that: The mass ratio of the carbon source to the original active material is 5% to 25%.

3. The method for preparing a positive electrode active material according to claim 1, characterized in that: The process parameters for plasma-assisted ball milling of the carbon source and the original active material include: the rotation speed of the ball mill is 900 rpm to 1000 rpm, the ball milling time is 30 min to 60 min, and the discharge current is 2A to 2.5A.

4. The method for preparing a positive electrode active material according to claim 1, characterized in that: The process parameters for plasma-assisted ball milling of the carbon source and the original active material include: a ball milling system, wherein the ball milling system includes: The plasma-assisted ball milling device works and stops alternately, a single working cycle duration of the plasma-assisted ball milling device is a working cycle duration, and a single stopping cycle duration of the plasma-assisted ball milling device is a stopping cycle duration.

5. The method for preparing a positive electrode active material according to claim 4, characterized in that: The working cycle duration ranges from 3 minutes to 8 minutes, and the stop cycle duration ranges from 3 minutes to 8 minutes.

6. The method for preparing a positive electrode active material according to claim 1, characterized in that: The ball milling medium in the ball milling jar is a grinding ball, and the diameter of the grinding ball is 2 mm to 5 mm; and / or the ball-to-material ratio of the ball milling is 5:1 to 10:

1.

7. The method for preparing a positive electrode active material according to claim 1, characterized in that: The process of sintering the precursor includes: Raising the temperature to a first calcination temperature at a first heating rate, and calcining at the first calcination temperature for a first preset time; The temperature is raised to a second calcination temperature at a second heating rate, and calcined at the second calcination temperature for a second preset time, and then annealed as the furnace is cooled, wherein the second calcination temperature is greater than the first calcination temperature.

8. The method for preparing a positive electrode active material according to claim 7, characterized in that: The first heating rate is 4°C / min to 6°C / min, the first calcination temperature is 280°C to 350°C, and the first calcination time is 2h to 3h; the second heating rate is 4°C / min to 6°C / min, the second calcination temperature is 560°C to 650°C, and the second calcination time is 3h to 5h.

9. The method for preparing a positive electrode active material according to claim 1, characterized in that: After adding the carbon source and the original active material into the ball milling tank of the plasma-assisted ball milling device and before subjecting the carbon source and the original active material to plasma-assisted ball milling, the method further comprises: The ball mill jar is subjected to a gas washing operation, which includes: evacuating the ball mill jar, and introducing argon gas after the evacuation, so that the gas pressure in the ball mill jar reaches a preset pressure.

10. The method for preparing a positive electrode active material according to claim 9, characterized in that: The scrubbing operation was repeated 2-3 times.

11. The method for preparing a positive electrode active material according to claim 9, characterized in that: The preset air pressure is 0.9-1.1 standard atmospheric pressure.

12. The method for preparing a positive electrode active material according to any one of claims 1 to 11, characterized in that: The carbon source includes DL-malic acid; and / or the original active material includes at least one of lithium iron phosphate, lithium manganese phosphate and lithium manganese iron phosphate.

13. A positive electrode active material, characterized in that: The positive electrode active material is prepared by the method for preparing a positive electrode active material according to any one of claims 1 to 12, the positive electrode active material comprises positive electrode active material particles, the positive electrode active material particles comprise a core and a carbon coating layer, and the carbon coating layer is coated on the outer surface of the core.

14. A battery, characterized in that: include: A positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode collector and a positive electrode active material covering the positive electrode collector, and the positive electrode active material is the positive electrode active material according to claim 13.

15. An electrical device, characterized in that: include: A battery according to claim 14.